Experimental and theoretical investigations into the mechanism of interactions between membrane-bound fatty acids and their binding protein: A model system to investigate the behavior of lipid acyl chains in contact with proteins. (September 2022) - Sugiyama, Shigeru; Matsuoka, Daisuke; Hara, Toshiaki; Sonoyama, Masashi; Matsuoka, Shigeru; Murata, Michio
Abstract: The interaction of proteins with hydrophobic ligands in biological membranes is an important research topic in the life sciences. The hydrophobic nature of ligands, especially their lack of water solubility, often makes it difficult to experimentally investigate their interactions with proteins, thus hampering quantitative evaluation based on thermodynamic parameters. The fatty acid-binding proteins, particularly FABP3, discussed in this review can recognize fatty acids, a primary component of membrane lipids, with high affinity. The precise three-dimensional structure of fatty acids and related ligands bound in FABP3 and their interaction with the binding pocket will contribute to the understanding of accurately determining physicochemical factors that cause the expression of affinity between protein surfaces and lipids in biological membranes. During the research of FABP3, we encountered many of the problems that were widely implicated in experiments dealing with hydrophobic ligands. To address these issues, we developed experimental methodologies using X-ray crystallography, calorimetry, and surface plasmon resonance. Using these methods and computational approaches, we have obtained several insights into the interaction of hydrophobic ligands with protein binding sites. Structural and functional studies of FABP potentially lead to a better understanding of the interaction between lipids and proteins, and thus, this protein may provide one of the model systems for investigating substance transport across cell membranes and inner membrane systems. Highlights: The affinity of fatty acid binding protein 3 (FABP3) was evaluated for diverse fatty acids using liposomes and calorimetry. High-resolution X-ray crystallography disclosed the precise 3D structure of fatty acid with various lengths in FABP3. Water molecules in the binding pocket of FABP3 serve to bind fatty acids of different lengths with similar affinity. Both the portal α-helix and β-barrel of FABP3 open to allow the smooth exchange of water and fatty acids.